2020
DOI: 10.1016/j.isci.2020.101857
|View full text |Cite
|
Sign up to set email alerts
|

Super-Enhancer LncRNA LINC00162 Promotes Progression of Bladder Cancer

Abstract: Due to the lack of effective early diagnostic measures and treatment methods, bladder cancer has become a malignant tumor that seriously threatens people's lives and health. Here, we reported that LINC00162, a super-enhancer long noncoding RNA, was highly expressed in bladder cancer cells and tissues. And LINC00162 was negatively correlated with neighboring PTTG1IP expression. Knocking down LINC00162 expression can inhibit the proliferative activity of bladder cancer cells and the growth of transplanted tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In addition to these scenarios, we recently showed that gain‐of‐function mutation in the seed sequences of miRNA‐140, driven by chondrocyte‐specific super‐enhancers, causes autosomal dominant human skeletal dysplasia (“spondyloepiphyseal dysplasia MIR140 type Nishimura”), extending the roles of super‐enhancers in human diseases 7,8 . Although the association between super‐enhancers and long non‐coding RNAs (lncRNAs) in cell identity control has not been explored in depth, certain super–enhancer‐driven lncRNAs (SE‐lncRNAs) have been implicated in cancer pathogenesis 9‐16 . Multifaceted functional crosstalk between super‐enhancers and lncRNAs, including cis and trans gene or super‐enhancer regulation by lncRNAs, has been also suggested 9,13,17,18 …”
Section: Super‐enhancers and Cancer Biologymentioning
confidence: 99%
“…In addition to these scenarios, we recently showed that gain‐of‐function mutation in the seed sequences of miRNA‐140, driven by chondrocyte‐specific super‐enhancers, causes autosomal dominant human skeletal dysplasia (“spondyloepiphyseal dysplasia MIR140 type Nishimura”), extending the roles of super‐enhancers in human diseases 7,8 . Although the association between super‐enhancers and long non‐coding RNAs (lncRNAs) in cell identity control has not been explored in depth, certain super–enhancer‐driven lncRNAs (SE‐lncRNAs) have been implicated in cancer pathogenesis 9‐16 . Multifaceted functional crosstalk between super‐enhancers and lncRNAs, including cis and trans gene or super‐enhancer regulation by lncRNAs, has been also suggested 9,13,17,18 …”
Section: Super‐enhancers and Cancer Biologymentioning
confidence: 99%
“…lncRNA HCCL5 is an SE-driven gene that confers the malignant phenotypes of liver cancer cells [ 105 ]. LINC00162, an SE lncRNA, was highly expressed in bladder cancer cells and tissues, which can promote progression of bladder cancer [ 106 ]. Our team constructed prognostic models for five -genes associated with SEs for osteosarcoma patients and multiple myeloma patients, which accurately predict the prognosis of these cancer patients [ 107 , 108 ].…”
Section: Structures and Functions Of Sesmentioning
confidence: 99%
“…SNHG14 increases the growth and metastasis of BCa and inhibits apoptosis by regulating the miR-211-3p/ESM1 axis [ 88 ]. LINC00162 can regulate PTTG1IP expression by binding THRAP3 to promote cell proliferation and inhibit apoptosis [ 89 ]. Other lncRNAs, such as SNHG7 [ 90 , 91 ], ANRIL [ 92 ], ZEB2-AS1 [ 93 ], OIP5-AS1 [ 94 ], and PART1 [ 95 ], also have the same effects.…”
Section: Cell Apoptosismentioning
confidence: 99%